2017
DOI: 10.1590/1980-5373-mr-2016-0985
|View full text |Cite
|
Sign up to set email alerts
|

Study of Coffee Grounds Oil Action in PVC Matrix Exposed to Gamma Radiation: Comparison of Systems in Film and Specimen Forms

Abstract: The poly (vinyl chloride), PVC, undergoes changes in its physicochemical properties when it is exposed to gamma radiation. Thus, the radiolytic stabilization of PVC is one way for obtain a material with radiation resistance. In this work, we studied the coffee grounds oil as PVC radiolytic protection in two systems forms: PVC film and PVC specimen. The systems were irradiated at sterilization dose of medical devices and viscosity measurements were performed. According to viscosity assays of PVC films, there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Certain PVC-based composites have been already produced with the use of SCG oil; these composites showed resistance to gamma radiation. The authors suggested that this property of PVC produced with SCG oil can be very useful for the packaging of materials that undergo gamma radiation sterilization [46]. The authors [19] observed that coffee oil addition below 0.2% to bioactive films of carboxymethyl cellulose did not yield significant changes in the mechanical properties of experimentally produced films.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain PVC-based composites have been already produced with the use of SCG oil; these composites showed resistance to gamma radiation. The authors suggested that this property of PVC produced with SCG oil can be very useful for the packaging of materials that undergo gamma radiation sterilization [46]. The authors [19] observed that coffee oil addition below 0.2% to bioactive films of carboxymethyl cellulose did not yield significant changes in the mechanical properties of experimentally produced films.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of coffee waste, such as SCG oil, is fortifying the final product and at the same time is making SCG, a waste product, a valuable raw material. Literature supports the recognition of SCG oil as valuable in the production of biopolymers [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biodegradable packaging can be fortified with the inclusion of coffee waste, such as SCG, while at the same time SCG, a waste product, becomes a valuable raw material. The use of SCG in the creation of biopolymers is acknowledged in the literature [22].…”
Section: Resultsmentioning
confidence: 99%